Mangrove community structure in the coastal waters of Sehati Village, Central Maluku Regency - Namakule, Umar; Melsasail, Karel Markus (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANA, 2021)
Sehati is one of the villages located in Central Maluku Regency which has a mangrove area with an area of 66,5 ha which is used as a local tourist attraction. Tourism support facilities are built to improve the aesthetics of the area but have implications for the conversion of mangrove land. Mangrove cover is reduced due to logging by local communities and the intensity of plastic waste in the area has increased along with the low awareness of visitors. These tourism activities put significant pressure on the mangrove ecosystem in Sehati village. The purpose of this study was to analyze the community structure and environmental conditions of the substrate and waters in the mangrove forest area in Sehati village, Central Maluku Regency. Data collection was performed using the linear squared transect method. The transects used are 5 pieces with squared measuring 3 x 3 meter as many as 10 pieces and are supported of various parameters oh water physics and chemistry. There are 5 species of mangroves found in the coastal village waters. The diversity index value is low (0,348), the dominance index is high (0,893), and the evenness index is low (0,348). Rhizophora apiculata has the highest value of density (12,78 ind/m2), abundance (23 ind/m2), attendance frequency (0,96%), and index of importance (103,56). Physical and chemical conditions of waters are still in a good condition for the growth of magroves.